Kaleidoscope (New York, 2008)
Kaleidoscope, an Open Court Intervention Program, aids students whose reading level is two or more grades below their chronological grade level. Kaleidoscope condenses the essence of Open Court Reading in order to intensify the instruction, making it possible to deliver two years of instruction in one year.
Keywords: Children's stories, American.,Conduct of life,Văn học thiếu nhi, Mỹ,Ứng xử của cuộc sống; Fiction,Tiểu thuyết